2021
DOI: 10.1177/21676968211058501
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating and Binge Drinking in Emerging Adults During COVID-19 Lockdown in Italy: An Examination of Protective and Risk Factors

Abstract: This study investigated binge behaviors during COVID-19 lockdown in Italy, exploring individual and contextual risk factors. Participants were 1925 emerging adults ( M age = 24.18, SD age = 2.75; 71.9% women), recruited during the national lockdown in Italy. An online survey investigated binge behaviors both prior and during quarantine. Binge drinking significantly diminished during quarantine, while binge eating episodes did not vary in frequency. However, participants with pre-existent binge eating disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…This study also confirms an increase in binge eating compared to pre-pandemic. These results support the findings of an Italian study on pre-existing binge eating disorders exacerbated during COVID-19 lockdown [ 24 ]. Higher stresses related to the pandemic and awareness of weakened support systems may increase binge eating behavior.…”
Section: Discussionsupporting
confidence: 90%
“…This study also confirms an increase in binge eating compared to pre-pandemic. These results support the findings of an Italian study on pre-existing binge eating disorders exacerbated during COVID-19 lockdown [ 24 ]. Higher stresses related to the pandemic and awareness of weakened support systems may increase binge eating behavior.…”
Section: Discussionsupporting
confidence: 90%
“…On this subscale, questions investigate the frequency with which compensatory behaviors are engaged around alcohol consumption episodes, with answers rated on a Likert-type scale ranging from 1 ( never ) to 5 ( always ). The DMBS has been shown to have good psychometric properties in the Italian context [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. In the present study, the instrument showed high reliability (Cronbach’s alpha = 0.97).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the protective effects of emotional and social support were reduced by the forced isolation. As a consequence, there was an increase in the incidence of eating disorders characterized by binge and restrictive behaviors (e.g., bulimia nervosa and anorexia, respectively) [ 33 , 34 , 35 , 36 , 37 , 38 ], and a worsening of symptoms in individuals who had already been experiencing these conditions [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, which were not meta-analysed due to their limited number, revealed increased levels of overeating from pre-pandemic to pandemic time [ 75 , 76 ], and snacking [ 75 ]. No change in body shape concerns [ 46 , 77 ], body weight reduction [ 44 , 78 ], and binge eating was observed [ 79 , 80 ]. Only one study [ 81 ] reported decreased levels of binge eating during the second wave of the pandemic compared to the first wave.…”
Section: Resultsmentioning
confidence: 99%